FACTORS THAT INFLUENCE FINANCIAL PERFORMANCE WITH DIVIDEND POLICY AS A MODERATING VARIABLE - Linda, Linda; Yanti, Yanti (International Journal of Application on Economics and Business, 2024)
This study aims to analyze the effect of liquidity, leverage, and profitability simultaneously and partially on company value moderated by dividend policy. This research was conducted on mining companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. The sample in this study was seleceted using purposive sampling which resulted in 8 companies from 14 companies listed on Stock Exchange (IDX). The hypothesis testing method in this study uses a panel data regression model with a Fixed Effect Model approach. Analysis of the model using the Eviews program version 12. The results showed that liquidity and profitability has a positive and significant effect on company value. But leverage has a negative and insignificant effect on company value. Then dividend policy is unable to moderate (weaken) the effect of liquidity and leverage on company value. However, dividend policy is able to moderate (strengthen) the effect of profitability on company value.